Numerical modeling and experimental investigation of laser-assisted machining of silicon nitride ceramics - Shen, Xinwei (Kansas State University, 2010)
Laser-assisted machining (LAM) is a promising non-conventional machining technique for advanced ceramics. However, the fundamental machining mechanism which governs the LAM process is not well understood so far. Hence, the main objective of this study is to explore the machining mechanism and provide guidance for future LAM operations. In this study, laser-assisted milling (LAMill) of silicon nitride ceramics is focused. Experimental experience reveals that workpiece temperature in LAM of silicon nitride ceramics determines the surface quality of the machined workpiece. Thus, in order to know the thermal features of the workpiece in LAM, the laser-silicon nitride interaction mechanism is investigated via heating experiments. The trends of temperature affected by the key parameters (laser power, laser beam diameter, feed rate, and preheat time) are obtained through a parametric study. Experimental results show that high operating temperature leads to low cutting force, good surface finish, small edge chipping, and low residual stress. The temperature range for brittle-to-ductile transition should be avoided due to the rapid increase of fracture toughness. In order to know the temperature distribution at the cutting zone in the workpiece, a transient three-dimensional thermal model is developed using finite element analysis (FEA) and validated through experiments. Heat generation associated with machining is considered and demonstrated to have little impact on LAM. The model indicates that laser power is one critical parameter for successful operation of LAM. Feed and cutting speed can indirectly affect the operating temperatures. Furthermore, a machining model is established with the distinct element method (or discrete element method, DEM) to simulate the dynamic process of LAM. In the microstructural modeling of a β-type silicon nitride ceramic, clusters are used to simulate the rod-like grains of the silicon nitride ceramic and parallel bonds act as the intergranular glass phase between grains. The resulting temperature-dependent synthetic materials for LAM are calibrated through the numerical compression, bending and fracture toughness tests. The machining model is also validated through experiments in terms of cutting forces, chip size and depth of subsurface damage.
Keywords: laser-assisted machining; silicon nitride; numerical modeling; ceramics; Engineering, Industrial (0546); Engineering, Materials Science (0794); Engineering, Mechanical (0548)